The grammatical realization of polarity contrast theoretical, empirical, and typological approaches - Dimroth, Christine; Sudhoff, Stefan, 1977- (Linguistik aktuell/Linguistics today (LA), 2018)
"The polarity of a sentence is crucial for its meaning. It is thus hardly surprising that languages have developed devices to highlight this meaning component and to contrast statements with negative and positive polarity in discourse. Research on this issue has started from languages like German and Dutch, where prosody and assertive particles are systematically associated with polarity contrast. Recently, the grammatical realization of polarity contrast has been at the center of investigations in a range of other languages as well. Core questions concern the formal repertoire and the exact meaning contribution of the relevant devices, the kind of contrast they evoke, and their relation to information structure and sentence mood. This volume brings together researchers from a theoretical, an empirical, and a typological orientation and enhances our understanding of polarity with the help of in-depth analyses and cross-linguistic comparisons dealing with the syntactic, semantic, pragmatic and/or prosodic aspects of the phenomenon"--